Enhancing Primary Students’ Achivement in Civic Education with Talking Stick Approach - Noviana, Eddy; Desta, Cindy Triwulan (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This study aims to determine differences in student learning outcomes learned through cooperative learning model type of talking stick with students who are taught conventional learning model. This research uses quasi experimental method with nonequivalent control group design. This research was conducted at 62 students in third class elementary school. The result of the research is before implemntation cooperative type learning model talking stick type in the experimental class and conventional model learning in the control class is obtained tcount<ttabel that is -0.430 <2.000 which means there is no significant difference civic education learning outcome. In the experimental class and control class after treatment obtained tcount<ttabel is 0.676 <2.000 which also means there is no difference civic education learning outcome. Thus, it can be conclude that cooperative learning model with talking stick can enhance elementary students’ achivement in civic education.